1995
DOI: 10.1152/ajpgi.1995.268.4.g631
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and localization of the insulin-like growth factor system in small bowel during altered nutrient status

Abstract: Insulin-like growth factor-I (IGF-I) may regulate small bowel growth. Analyses here in ad libitum-fed, fasted, and refed rats demonstrate that during fasting and refeeding changes in jejunal mass correlate with changes in serum IGF-I and jejunal IGF-I mRNAs. These data indicate that circulating and locally expressed IGF-I contribute to nutrient regulation of jejunal mass. During refeeding, jejunal IGF binding protein 3 (IGFBP-3) mRNA abundance was reduced relative to that of IGF-I, possibly amplifying enterotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 0 publications
10
65
1
5
Order By: Relevance
“…Specifically, the intestinal phenotype of CF mice histologically resembles that of rats after major small bowel resection wherein changes in the ileum include muscle wall hypertrophy and villus enlargement (21). Igfbp-3 mRNA levels in the intestine are decreased after major small bowel resection (22) or after postfast refeeding, where the decrease coincides with a similar growth response in the intestinal mucosa (10). Second, Gillingham et al (23) reported increased expression of Igf-1 and Igfbp-5, which were also more highly expressed in the CF intestine, in sections of intestinal growth of a jejunoileal resection model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the intestinal phenotype of CF mice histologically resembles that of rats after major small bowel resection wherein changes in the ileum include muscle wall hypertrophy and villus enlargement (21). Igfbp-3 mRNA levels in the intestine are decreased after major small bowel resection (22) or after postfast refeeding, where the decrease coincides with a similar growth response in the intestinal mucosa (10). Second, Gillingham et al (23) reported increased expression of Igf-1 and Igfbp-5, which were also more highly expressed in the CF intestine, in sections of intestinal growth of a jejunoileal resection model.…”
Section: Discussionmentioning
confidence: 99%
“…Igf-I is regulated by a family of proteins, known as the IGF-binding proteins (IGFBPs), which modulate Igf-I action either by presenting Igf-I to its receptor or by sequestering the peptide and reducing receptor interaction (8). Igfbp-3 accounts for 80% of IGF binding in the circulation (9) and may modulate Igf-I action in the intestine (10). Independent of the Igf-I interaction, increased levels of Igfbp-3 have been shown to inhibit the proliferation of intestinal smooth muscle cells (11) and to induce apoptosis in colonic adenoma-derived cells (12).…”
Section: Ystic Fibrosis (Cf) Is Caused By Mutations In the Cfmentioning
confidence: 99%
“…Early weaning, altered nutrient status, and changing of diets can severely affect patterns of early growth and related hormone secretion, and refeeding may effectively restore normal physiologic and physical development [50,51] Circulating growth factors, such as IGF-1, have been implicated in the control of the intestinal epithelial proliferation and influencing cell migration and differentiation on in vitro and in vivo models of intestinal healing [33], effects that may be stimulated and regulated by critical nutrients [52] upon refeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional status also regulates expression of various endogenous intestinal growth factors, including insulinlike growth factor-I and KGF and its receptor (9,44,(47)(48)(49). However, there have been few studies on nutrient regulation of intestinal goblet cells (6,30,35,37) or TFF peptide expression.…”
mentioning
confidence: 99%